How to prove this? Let z = a + ib be a complex number. Show that a square root of z is given by the expression w=sqrt((|z|+a)/2)+iσ*sqrt((|z|-a)/2) where σ = 1 if b ≥ 0 and σ = −1 if b < 0. Do this by verifying that w^2=z ?

w=sqrt((|z|+a)/2)+iσ*sqrt((|z|-a)/2)
w^2=z

1 Answer
Mar 18, 2018

See below.

Explanation:

Calling

sqrtz = u + i v we have

(u+iv)^2 = z = a+ib or

{(u^2-v^2=a),(2uv=b):}

now solving for u,v

{(u = sqrt[(sqrt[ a^2 + b^2]+a)/2]), (v =b/(sqrt[2] sqrt[sqrt[a^2 + b^2]+a])):}

but

b/(sqrt[2] sqrt[sqrt[a^2 + b^2]+a]) = (bsqrt[sqrt[a^2 + b^2]-a])/(sqrt[2] sqrt(a^2+b^2-a^2)) = b/sqrt(b^2)sqrt[(sqrt[a^2 + b^2]-a)/2]=sigma(b)sqrt[(sqrt[a^2 + b^2]-a)/2]

where

sigma(b) = b/abs(b)

Finally, considering absz = sqrt(a^2+b^2) we have

w=sqrt((|z|+a)/2)+iσ(b)sqrt((|z|-a)/2)